The role of the nordic dimension for foreign trade relations of baltic states - Kairi Andresson; Janno Reiljan; Ele Reiljan (European Regional Science Association (ERSA), 2001)
Baltic Sea Region (BRS) can be seen as one good example of an attempt to integrate countries with different development levels. In the long run the Baltic Sea could be seen as the internal sea of European Union. However, as different are the development stages of BRS countries, different is their co-operation experience with European Union (EU). Foreign trade can be seen as one possibility for facilitating economic cooperation between countries. Foreign trade must have a positive impact on economic development of trading partners, when they are equal in the level of development, and foster economic growth even then, when their are unequal. Nevertheless, the one assumption of the theory is a free trade, but this assumption is not always fulfilled. Baltics as small transition countries have from one side not many possibilities for influencing foreign trade, because we are price and conditions takers. From other side, we are small enough to get more favourable conditions in trading with economic blocks and developed countries. Nevertheless, the better conditions compared to other third and associated countries, that we achieved for trading with EU, do not guarantee automatically higher volumes and more equal conditions in trade with above mentioned countries. Encouraging is the fact that European Union Council has approved the Action Plan for the Northern Dimension with external and cross-border policies of the European Union 2000-2003. The aim of current paper is to analyse the current situation in foreign trade of three Baltic States (Estonia, Latvia, Lithuania) in the context of fostering economic co-operation in Nordic Dimension. To accomplish this aim: - We analyse the openness or closeness of the trade in Baltic Sea region, find out its positive and negative aspects. -We will look at geographical distribution of foreign trade of three Baltics and analyse it. -We analyse the commodity structure of foreign trade of three Baltics with countries in BSR. -We will analyse the possibilities and risks of current situation in Baltics' foreign trade in the context of economic globalisation and integration. Data of national statistic bureaus and national banks will be used for comparing the situation in Baltics' foreign trade. The analysis will not cover transit trade and trade with services.
Keywords: 330